Implementing ARVi media to enhance students high order cognitive skills - Risda Putri Indriani; Tri Handayani Kurniati; Rizhal Hendi Ristanto (University of Muhammadiyah Malang, 2024)
High-order cognitive skills (HOCS) are required to solve problems and make decisions. ARVi or augmented reality virus is a learning medium used to enhance HOCS. Aims of this research is to find out the effect of implementing ARVi media on enhancing high-level cognitive skills of students. The research is a quasi-experiment with a pretest-posttest control group design. The research was conducted in MAN 1 Kota Bogor class 10 using the Merdeka curriculum. The research instrument is a multiple-choice test that has been validated to measure high-level cognitive skills. The result of the t-test shows t-value (3.14) > t-table (1.98), indicating that there is a significant difference between the posttest scores of the control group and the experimental group. This means that the use of ARVi media has an effect on high-level cognitive skills. The improvement in high-level cognitive skills was continuous in C5 (evaluation) at 78%, C6 (creation) at 72%, and C4 (analysis) at 70%. These results are not independent of the support provided by the various content offered by ARVi media, such as augmented reality, literacy, and high-level questionnaires. Current education can benefit from technologies like ARVi media that help increase the high-level cognitive skills of students.